PENGARUH KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PPKn KELAS X - Rima Mawar; Achmadi Achmadi; Bambang Budi Utomo (Universitas Tanjungpura, 2019)
AbstractThis researcher was conducted with a descriptive research method using a quantitative approach. The results of the research and discussion, the following conclusions can be drawn: 1) The level of emotional intelligence of class X students of SMA Negeri 1 Sungai Raya, Kubu Raya Regency is generally included in the medium category with a percentage of 59.52%. 2) Learning outcomes of PPKn students of X high school Negeri 1 in general is included in the medium category with a percentage of 71.43% 3) There is no significant influence of emotional intelligence on student learning outcomes in class X SMA Negeri 1 Sungai Raya. This is seen from the results of the analysis using a regression test proving that the regression equation obtained Y = 87.818 + 0.02X. From the significant test results obtained a significant value of 0.985 where a significant value of 0.05 (0.985 0.05), then accepted. So it can be concluded that there is no significant influence of emotional intelligence on learning outcomes. It is recommended for PPKn teachers to try to improve in the students they teach about positive emotional intelligence. This can be pursued through the growth in each student regarding recognizing emotions, managing emotions, motivating oneself, empathy and being able to foster relationships (social skills). Keyword : Emotional Intelligence, Learning Outcomes, High School Students